Ne Jamais Avouer (May Moore Suspense Thriller, ,, 2024)
Blake Pierce, auteur de best-sellers rempli de suspense et de mystère, nous offre une nouvelle série captivante : May Moore, 29 ans, femme banale du Midwest et shérif adjointe, a toujours vécu dans l'ombre de sa brillante sœur aînée, agent du FBI. Pourtant, les deux sœurs sont unies par la disparition de leur cadette. Lorsqu'un tueur en série étrangement similaire frappe dans la ville tranquille du Minnesota o vit May, c'est à son tour de faire ses preuves. Dans ce thriller débordant d'action, elle essaiera de surpasser sa sœur ainsi que le FBI, de traquer un tueur diabolique et de déjouer ses plans avant qu'il ne frappe à nouveau. « Un chef-d'œuvre de thriller et de mystère. » Roberto Mattos, Books and Movie Reviews (pour SANS LAISSER DE TRACES) Des victimes sont retrouvées mortes près d'une nouvelle chaîne d'htels huppés qui a acheté des propriétés au bord du lac et rendu les habitants furieux. Les fausses pistes sont légion, mais l'adjointe au shérif May Moore pense que le mobile du tueur pourrait être bien plus complexe. Et que ce meurtrier pourrait être bien plus sinistre qu'on ne le croit. Pendant ce temps, sa sœur ainée, agent accomplie de l'Unité d'analyse du comportement du FBI, rentre à la maison avec une nouvelle choquante qui bouleverse la vie de May. Au même moment, de nouvelles preuves font leur apparition dans l'enquête sur la mort de leur sœur. May va néanmoins devoir jongler avec ces informations car un tueur est en cavale et ne s'arrêtera pas avant d'avoir été traduit en justice. May est-elle à la hauteur ? Ou deviendra-t-elle sa prochaine cible ? La série MAY MOORE est un thriller policier passionnant et déchirant, mettant en scène une brillante et torturée adjointe au shérif, un mystère fascinant, plein d'action, de suspense et des rebondissements à couper le souffle, le tout à un rythme effréné qui vous fera tourner les pages jusque tard dans la nuit. Le tome #3 de la série NE JAMAIS VIVRE est aussi disponible. « Un thriller dans une nouvelle série qui vous tiendra en haleine et vous fera tourner les pages ! Plein de rebondissements, de retournements et de fausses pistes... J'ai hâte de voir ce qui va se passer ensuite. » Critique d'un lecteur (SON DERNIER SOUHAIT) « Une histoire forte et complexe sur deux agents du FBI qui tentent d'arrêter un tueur en série. Si vous cherchez un auteur qui capte votre attention et vous fait réfléchir en essayant de rassembler les pièces du puzzle, Pierce est votre homme ! » Critique d'un lecteur (SON DERNIER SOUHAIT) « Un thriller à suspense typique de Blake Pierce, avec ses rebondissements et ses montagnes russes. Il vous fera tourner les pages jusqu'à la dernière phrase du dernier chapitre ! » Critique d'un lecteur (LA VILLE DES PROIES) « Dès le début, nous avons un protagoniste inhabituel que je n'ai jamais vu dans ce genre auparavant. L'action est non-stop... Un roman très atmosphérique qui vous fera tourner les pages jusqu'au petit matin. » Critique d'un lecteur (LA VILLE DES PROIES) « Tout ce que je recherche dans un livre : une grande intrigue et des personnages forts qui captent tout de suite votre intérêt. Le livre avance à un rythme effréné jusqu'à la fin. Je vais de suite passer au livre deux ! » Critique d'un lecteur (LA FILLE, SEULE) « Un livre passionnant qui vous fait battre le cœur et vous rive à votre siège... À lire absolument pour les amateurs de mystère et de suspense ! » Critique d'un lecteur (LA FILLE, SEULE)

Ne Jamais Fuir (May Moore Suspense Thriller, ,, 2024)
Blake Pierce, auteur de best-sellers rempli de suspense et de mystère, nous offre une nouvelle série captivante : May Moore, 29 ans, femme banale du Midwest et shérif adjointe, a toujours vécu dans l'ombre de sa brillante sœur aînée, agent du FBI. Pourtant, les deux sœurs sont unies par la disparition de leur cadette. Lorsqu'un tueur en série étrangement similaire frappe dans la ville tranquille du Minnesota o vit May, c'est à son tour de faire ses preuves. Dans ce thriller débordant d'action, elle essaiera de surpasser sa sœur ainsi que le FBI, de traquer un tueur diabolique et de déjouer ses plans avant qu'il ne frappe à nouveau. « Un chef-d'œuvre de thriller et de mystère. » Roberto Mattos, Books and Movie Reviews (pour SANS LAISSER DE TRACES) May Moore ne perd pas de temps pour enquêter, mais les choses dérapent vite lorsque sa sœur aînée est appelée en renfort. Agent accomplie de l'Unité d'analyse du comportement du FBI, celle-ci passe son temps à lui faire de l'ombre. Comble de malchance, l'enquête fait remonter à la surface de terribles souvenirs et secrets enfouis sur le passé de leur famille. Ni May, ni sa sœur ne sont prêtes à les affronter. Mais le compte à rebours est lancé, May et sa sœur devront mettre leurs vieilles rancœurs de cté pour trouver ce tueur et sauver sa prochaine victime. Elles devront faire attention à ne pas se laisser emporter et penser que ce meurtrier est le même que celui de leur passé. Mais est-ce lui ? La série MAY MOORE est un thriller policier passionnant et déchirant, mettant en scène une brillante et torturée adjointe au shérif, un mystère fascinant, plein d'action, de suspense et des rebondissements à couper le souffle, le tout à un rythme effréné qui vous fera tourner les pages jusque tard dans la nuit. Tomes #2 et #3 de la série NE JAMAIS AVOUER et NE JAMAIS VIVRE sont aussi disponibles. « Un thriller dans une nouvelle série qui vous tiendra en haleine et vous fera tourner les pages ! Plein de rebondissements, de retournements et de fausses pistes... J'ai hâte de voir ce qui va se passer ensuite. » Critique d'un lecteur (SON DERNIER SOUHAIT) « Une histoire forte et complexe sur deux agents du FBI qui tentent d'arrêter un tueur en série. Si vous cherchez un auteur qui capte votre attention et vous fait réfléchir en essayant de rassembler les pièces du puzzle, Pierce est votre homme ! » Critique d'un lecteur (SON DERNIER SOUHAIT) « Un thriller à suspense typique de Blake Pierce, avec ses rebondissements et ses montagnes russes. Il vous fera tourner les pages jusqu'à la dernière phrase du dernier chapitre ! » Critique d'un lecteur (LA VILLE DES PROIES) « Dès le début, nous avons un protagoniste inhabituel que je n'ai jamais vu dans ce genre auparavant. L'action est non-stop... Un roman très atmosphérique qui vous fera tourner les pages jusqu'au petit matin. » Critique d'un lecteur (LA VILLE DES PROIES) « Tout ce que je recherche dans un livre : une grande intrigue et des personnages forts qui captent tout de suite votre intérêt. Le livre avance à un rythme effréné jusqu'à la fin. Je vais de suite passer au livre deux ! » Critique d'un lecteur (LA FILLE, SEULE) « Un livre passionnant qui vous fait battre le cœur et vous rive à votre siège... À lire absolument pour les amateurs de mystère et de suspense ! » Critique d'un lecteur (LA FILLE, SEULE)

Ne Jamais Se Cacher (May Moore Suspense Thriller, ,, 2023)
Blake Pierce, auteur à succès de mystère et de suspense, nous livre une nouvelle saga : May Moore, 29 ans, banale femme du Midwest américain et shérif adjointe, a toujours vécu dans l'ombre de sa sœur ainée, brillante agent du FBI. Néanmoins, les deux sœurs se retrouvent unies par la réouverture de l'enquête sur la disparition de leur cadette. Et lorsqu'un nouveau tueur en série frappe la ville tranquille du Minnesota o vit May, c'est à son tour de prouver sa valeur et de tenter de dépasser sa sœur et le FBI. Dans ce thriller débordant d'action, elle devra déjouer les plans d'un tueur diabolique et l'attraper avant qu'il ne frappe à nouveau. « Un chef-d'œuvre de thriller et de mystère. » Roberto Mattos, Books and Movie Reviews (pour SANS LAISSER DE TRACES) Un cadavre est découvert en train de flotter paisiblement sur le lac dans la ville de May. Rapidement, d'autres corps apparaissent. Ce cadavre semble trop paisible, ce meurtre trop tranquille. May pourra-t-elle pénétrer l'esprit du tueur et résoudre l'affaire avant qu'il ne fasse une nouvelle victime ? La série MAY MOORE est un thriller policier passionnant et déchirant, mettant en scène une brillante et torturée adjointe au shérif, un mystère fascinant, plein d'action, de suspense et des rebondissements à couper le souffle, le tout à un rythme effréné qui vous fera tourner les pages jusque tard dans la nuit. Les tomes 5 et 6 -Ne Jamais Pardonner et Ne Jamais Recommencer - sont aussi disponibles ! « Un thriller dans une nouvelle série qui vous tiendra en haleine et vous fera tourner les pages ! Plein de rebondissements, de retournements et de fausses pistes... J'ai hâte de voir ce qui va se passer ensuite. » Critique d'un lecteur (SON DERNIER SOUHAIT) « Une histoire forte et complexe sur deux agents du FBI qui tentent d'arrêter un tueur en série. Si vous cherchez un auteur qui capte votre attention et vous fait réfléchir en essayant de rassembler les pièces du puzzle, Pierce est votre homme ! » Critique d'un lecteur (SON DERNIER SOUHAIT) « Un thriller à suspense typique de Blake Pierce, avec ses rebondissements et ses montagnes russes. Il vous fera tourner les pages jusqu'à la dernière phrase du dernier chapitre ! » Critique d'un lecteur (LA VILLE DES PROIES) « Dès le début, nous avons un protagoniste inhabituel que je n'ai jamais vu dans ce genre auparavant. L'action est non-stop... Un roman très atmosphérique qui vous fera tourner les pages jusqu'au petit matin. » Critique d'un lecteur (LA VILLE DES PROIES) « Tout ce que je recherche dans un livre : une grande intrigue et des personnages forts qui captent tout de suite votre intérêt. Le livre avance à un rythme effréné jusqu'à la fin. Je vais de suite passer au livre deux ! » Critique d'un lecteur (LA FILLE, SEULE) « Un livre passionnant qui vous fait battre le cœur et vous rive à votre siège... À lire absolument pour les amateurs de mystère et de suspense ! » Critique d'un lecteur (LA FILLE, SEULE)

Ne Jamais Vivre (May Moore Suspense Thriller, ,, 2023)
Blake Pierce, auteur de best-sellers rempli de suspense et de mystère, nous offre une nouvelle série captivante : May Moore, 29 ans, femme banale du Midwest et shérif adjointe, a toujours vécu dans l'ombre de sa brillante sœur aînée, agent du FBI. Pourtant, les deux sœurs sont unies par la disparition de leur cadette. Lorsqu'un tueur en série étrangement similaire frappe dans la ville tranquille du Minnesota o vit May, c'est à son tour de faire ses preuves. Dans ce thriller débordant d'action, elle essaiera de surpasser sa sœur ainsi que le FBI, de traquer un tueur diabolique et de déjouer ses plans avant qu'il ne frappe à nouveau. « Un chef-d'œuvre de thriller et de mystère. » Roberto Mattos, Books and Movie Reviews (pour SANS LAISSER DE TRACES) Une fête d'après bal de fin d'année au bord du lac a terriblement mal tourné. Une victime adolescente est retrouvée morte sur la rive. May s'efforce de comprendre et essaye de reconstituer cette soirée dont aucun des fêtards ne se souvient. La fête a-t-elle simplement échappé à tout contrle ? Ou cela pourrait-il être l'œuvre d'un nouveau tueur ? La série MAY MOORE est un thriller policier passionnant et déchirant, mettant en scène une brillante et torturée adjointe au shérif, un mystère fascinant, plein d'action, de suspense et des rebondissements à couper le souffle, le tout à un rythme effréné qui vous fera tourner les pages jusque tard dans la nuit. D'autres tomes de cette série seront bientt disponibles. « Un thriller dans une nouvelle série qui vous tiendra en haleine et vous fera tourner les pages ! Plein de rebondissements, de retournements et de fausses pistes... J'ai hâte de voir ce qui va se passer ensuite. » Critique d'un lecteur (SON DERNIER SOUHAIT) « Une histoire forte et complexe sur deux agents du FBI qui tentent d'arrêter un tueur en série. Si vous cherchez un auteur qui capte votre attention et vous fait réfléchir en essayant de rassembler les pièces du puzzle, Pierce est votre homme ! » Critique d'un lecteur (SON DERNIER SOUHAIT) « Un thriller à suspense typique de Blake Pierce, avec ses rebondissements et ses montagnes russes. Il vous fera tourner les pages jusqu'à la dernière phrase du dernier chapitre ! » Critique d'un lecteur (LA VILLE DES PROIES) « Dès le début, nous avons un protagoniste inhabituel que je n'ai jamais vu dans ce genre auparavant. L'action est non-stop... Un roman très atmosphérique qui vous fera tourner les pages jusqu'au petit matin. » Critique d'un lecteur (LA VILLE DES PROIES) « Tout ce que je recherche dans un livre : une grande intrigue et des personnages forts qui captent tout de suite votre intérêt. Le livre avance à un rythme effréné jusqu'à la fin. Je vais de suite passer au livre deux ! » Critique d'un lecteur (LA FILLE, SEULE) « Un livre passionnant qui vous fait battre le cœur et vous rive à votre siège... À lire absolument pour les amateurs de mystère et de suspense ! » Critique d'un lecteur (LA FILLE, SEULE)

Never Again (May Moore Suspense Thriller, ,, 2022)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. After a local manhunt for a missing woman, a pack of cadaver dogs lead police to the source. But when the dogs unearth body after body, May soon realizes she has stumbled upon a burial mound-and is up against a serial killer for more deadly than anyone could have imagined. With time running out, can May find him-before he finds her first? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night. Future books in the series will be available soon!

Never Forget (May Moore Suspense Thriller, ,, 2023)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. "A masterpiece of thriller and mystery." -Books and Movie Reviews, Roberto Mattos (re Once Gone) ⭐⭐⭐⭐⭐ When two victims are found dead in different vacation houses on the lake, an idyllic Midwestern retreat becomes a nightmare. The local politicians are soon in a panic-and for May, the pressure is on. But something isn't adding up about this case-and the answer may be right in the open. Can May enter the killer's mind and stop him before it's too late? Or will she walk straight into his trap? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night. Book #9 in the series-NEVER LET GO-is also available! "An edge of your seat thriller in a new series that keeps you turning pages! ...So many twists, turns and red herrings... I can't wait to see what happens next." -Reader review (Her Last Wish) ⭐⭐⭐⭐⭐ "A strong, complex story about two FBI agents trying to stop a serial killer. If you want an author to capture your attention and have you guessing, yet trying to put the pieces together, Pierce is your author!" -Reader review (Her Last Wish) ⭐⭐⭐⭐⭐ "A typical Blake Pierce twisting, turning, roller coaster ride suspense thriller. Will have you turning the pages to the last sentence of the last chapter!!!" -Reader review (City of Prey) ⭐⭐⭐⭐⭐ "Right from the start we have an unusual protagonist that I haven't seen done in this genre before. The action is nonstop... A very atmospheric novel that will keep you turning pages well into the wee hours." -Reader review (City of Prey) ⭐⭐⭐⭐⭐ "Everything that I look for in a book... a great plot, interesting characters, and grabs your interest right away. The book moves along at a breakneck pace and stays that way until the end. Now on go I to book two!" -Reader review (Girl, Alone) ⭐⭐⭐⭐⭐ "Exciting, heart pounding, edge of your seat book... a must read for mystery and suspense readers!" -Reader review (Girl, Alone) ⭐⭐⭐⭐⭐

Never Forgive (May Moore Suspense Thriller, ,, 2022)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. "A masterpiece of thriller and mystery." -Books and Movie Reviews, Roberto Mattos (re Once Gone) When bodies turn up, the work of a new serial killer, the case seems too easily solved. But when federal agents storm the killer's lair-only to have it go up in flames and take them with it-May soon realizes that the line is being quickly blurred between the hunter-and the hunted. A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night. Book #6 in the series-NEVER AGAIN-is also available! "An edge of your seat thriller in a new series that keeps you turning pages! ...So many twists, turns and red herrings... I can't wait to see what happens next." -Reader review (Her Last Wish) "A strong, complex story about two FBI agents trying to stop a serial killer. If you want an author to capture your attention and have you guessing, yet trying to put the pieces together, Pierce is your author!" -Reader review (Her Last Wish) "A typical Blake Pierce twisting, turning, roller coaster ride suspense thriller. Will have you turning the pages to the last sentence of the last chapter!!!" -Reader review (City of Prey) "Right from the start we have an unusual protagonist that I haven't seen done in this genre before. The action is nonstop... A very atmospheric novel that will keep you turning pages well into the wee hours." -Reader review (City of Prey) "Everything that I look for in a book... a great plot, interesting characters, and grabs your interest right away. The book moves along at a breakneck pace and stays that way until the end. Now on go I to book two!" -Reader review (Girl, Alone) "Exciting, heart pounding, edge of your seat book... a must read for mystery and suspense readers!" -Reader review (Girl, Alone)

Never Hide (May Moore Suspense Thriller, ,, 2022)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. "A masterpiece of thriller and mystery." -Books and Movie Reviews, Roberto Mattos (re Once Gone) A body is found floating peacefully in the lake in May's hometown, and soon, more begin to appear. This body seems too peaceful, the murder too eerily calm. Can May enter this killer's mind and crack the case before he claims his next victim? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night. Books #5 and #6 in the series-NEVER FORGIVE and NEVER AGAIN-are also available! "An edge of your seat thriller in a new series that keeps you turning pages! ...So many twists, turns and red herrings... I can't wait to see what happens next." -Reader review (Her Last Wish) "A strong, complex story about two FBI agents trying to stop a serial killer. If you want an author to capture your attention and have you guessing, yet trying to put the pieces together, Pierce is your author!" -Reader review (Her Last Wish) "A typical Blake Pierce twisting, turning, roller coaster ride suspense thriller. Will have you turning the pages to the last sentence of the last chapter!!!" -Reader review (City of Prey) "Right from the start we have an unusual protagonist that I haven't seen done in this genre before. The action is nonstop... A very atmospheric novel that will keep you turning pages well into the wee hours." -Reader review (City of Prey) "Everything that I look for in a book... a great plot, interesting characters, and grabs your interest right away. The book moves along at a breakneck pace and stays that way until the end. Now on go I to book two!" -Reader review (Girl, Alone) "Exciting, heart pounding, edge of your seat book... a must read for mystery and suspense readers!" -Reader review (Girl, Alone)

Never Hide (May Moore Suspense Thriller, ,, 2022)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. A body is found floating peacefully in the lake in May's hometown, and soon, more begin to appear. This body seems too peaceful, the murder too eerily calm. Can May enter this killer's mind and crack the case before he claims his next victim? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night.

Never Hide (May Moore Suspense Thriller, ,, 2022)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. A body is found floating peacefully in the lake in May's hometown, and soon, more begin to appear. This body seems too peaceful, the murder too eerily calm. Can May enter this killer's mind and crack the case before he claims his next victim? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night.

Never Let Go (May Moore Suspense Thriller, ,, 2023)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. "A masterpiece of thriller and mystery." -Books and Movie Reviews, Roberto Mattos (re Once Gone) When a victim narrowly escapes from an eerie, underground bunker near the lake, May must race to decode who is behind the crime-and who else is out there, waiting to saved. But as May goes deeper down the rabbit hole, she soon realizes this case-and this killer-are far more dangerous than they seem. And in the isolated Midwest outskirts, every horror is amplified. Can she find this elusive killer before another victim vanishes underground? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night. Future books in the series will be available soon! "An edge of your seat thriller in a new series that keeps you turning pages! ...So many twists, turns and red herrings... I can't wait to see what happens next." -Reader review (Her Last Wish) "A strong, complex story about two FBI agents trying to stop a serial killer. If you want an author to capture your attention and have you guessing, yet trying to put the pieces together, Pierce is your author!" -Reader review (Her Last Wish) "A typical Blake Pierce twisting, turning, roller coaster ride suspense thriller. Will have you turning the pages to the last sentence of the last chapter!!!" -Reader review (City of Prey) "Right from the start we have an unusual protagonist that I haven't seen done in this genre before. The action is nonstop... A very atmospheric novel that will keep you turning pages well into the wee hours." -Reader review (City of Prey) "Everything that I look for in a book... a great plot, interesting characters, and grabs your interest right away. The book moves along at a breakneck pace and stays that way until the end. Now on go I to book two!" -Reader review (Girl, Alone) "Exciting, heart pounding, edge of your seat book... a must read for mystery and suspense readers!" -Reader review (Girl, Alone)

Never Live (May Moore Suspense Thriller, ,, 2022)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. "A masterpiece of thriller and mystery." -Books and Movie Reviews, Roberto Mattos (re Once Gone) An after-prom party by the lake has gone horribly awry, with a teenage victim found dead on the shore. May struggles to connect the dots, trying to reconstruct an evening that none of the partiers can remember. Did the party simply spiral out of control? Or could this be the work a new killer? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night. Books #4-#6 are also available!

Never Live (May Moore Suspense Thriller, ,, 2024)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. An after-prom party by the lake has gone horribly awry, with a teenage victim found dead on the shore. May struggles to connect the dots, trying to reconstruct an evening that none of the partiers can remember. Did the party simply spiral out of control? Or could this be the work a new killer? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night.

Never Live (May Moore Suspense Thriller, ,, 2022)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. "A masterpiece of thriller and mystery." -Books and Movie Reviews, Roberto Mattos (re Once Gone) An after-prom party by the lake has gone horribly awry, with a teenage victim found dead on the shore. May struggles to connect the dots, trying to reconstruct an evening that none of the partiers can remember. Did the party simply spiral out of control? Or could this be the work a new killer? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night. Books #4-#6 are also available!

Never Look Back (May Moore Suspense Thriller, ,, 2023)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. "A masterpiece of thriller and mystery." -Books and Movie Reviews, Roberto Mattos (re Once Gone) When victims of a new killer turn up on the farms outside town, attacked by an unusual murder weapon-a scythe-May must rush to decode the meaning-and to stop the killer before he strikes again. As May begins to unearth stories of violence and secrets, she is drawn into an isolated and eerie world. Can she track down this killer before it's too late? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night. Books #8 and #9 in the series-NEVER FORGET and NEVER LET GO-are also available! "An edge of your seat thriller in a new series that keeps you turning pages! ...So many twists, turns and red herrings... I can't wait to see what happens next." -Reader review (Her Last Wish) "A strong, complex story about two FBI agents trying to stop a serial killer. If you want an author to capture your attention and have you guessing, yet trying to put the pieces together, Pierce is your author!" -Reader review (Her Last Wish) "A typical Blake Pierce twisting, turning, roller coaster ride suspense thriller. Will have you turning the pages to the last sentence of the last chapter!!!" -Reader review (City of Prey) "Right from the start we have an unusual protagonist that I haven't seen done in this genre before. The action is nonstop... A very atmospheric novel that will keep you turning pages well into the wee hours." -Reader review (City of Prey) "Everything that I look for in a book... a great plot, interesting characters, and grabs your interest right away. The book moves along at a breakneck pace and stays that way until the end. Now on go I to book two!" -Reader review (Girl, Alone) "Exciting, heart pounding, edge of your seat book... a must read for mystery and suspense readers!" -Reader review (Girl, Alone)

Never Run (May Moore Suspense Thriller, ,, 2022)
Van de #1 bestsellerauteur van mysterie en spanning Blake Pierce komt een spannende nieuwe serie: May Moore, 29, een doorsnee vrouw en hulpsheriff uit het midwesten, heeft altijd geleefd in de schaduw van haar oudere, briljante zus die FBI-agent is. Toch zijn de zusters verenigd door de onopgeloste zaak van hun vermiste jongere zus - en wanneer een griezelig vergelijkbare seriemoordenaar toeslaat in May's rustige stadje aan het meer in Minnesota, is het May's beurt om zichzelf te bewijzen, om te proberen haar zus en de FBI te overtreffen, en, in deze thriller boordevol actie, om een duivelse moordenaar te slim af te zijn en op te sporen voordat hij weer toeslaat. May Moore gaat meteen op onderzoek uit, maar het gaat al snel mis wanneer haar oudere zus, een ervaren FBI-agent gedragsanalyse die haar voortdurend overschaduwt, door de lokale autoriteiten wordt opgeroepen om te helpen. Erger nog, de zaak brengt duistere herinneringen en begraven geheimen uit haar familiegeschiedenis naar boven - en noch May noch haar zus zijn klaar om het verleden onder ogen te zien. Maar nu de klok doortikt, zullen May en haar zus oude grieven opzij moeten zetten om deze moordenaar op te sporen en het volgende slachtoffer te redden, en niet zomaar aannemen dat dit dezelfde moordenaar uit hun verleden is. Maar is hij dat? De MAY Moore-reeks is een razend spannende en aangrijpende misdaadthriller met een briljante en geteisterde hulpsheriff. Het biedt een meeslepend mysterie, constante actie, spanning, verbluffende wendingen en een razend tempo dat ervoor zorgt dat je tot diep in de nacht blijft doorlezen. Boeken #2 en #3 uit de reeks - VERTEL HET NOOIT en NOOIT MEER LEVEN - zijn ook verkrijgbaar.

Never Run (May Moore Suspense Thriller, ,, 2022)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when an eerily similar serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. May Moore wastes no time investigating, but things quickly go south when her older sister, an accomplished FBI BAU agent who constantly outshines her, is called in by local authorities to help. Making matters worse, the case brings up dark memories and buried secrets from her family's history-and neither May nor her sister are ready to confront the past. But with a ticking clock, May and her sister will have to put aside old grievances to find this killer and save the next victim, and they will have to be careful not to assume this is the same killer from their past. But is he? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night. Books #2 and #3 in the series-NEVER TELL and NEVER LIVE-are also available.

Never Run (May Moore Suspense Thriller, ,, 2022)
From number one best-selling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when an eerily similar serial killer strikes in May's quiet Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. May Moore wastes no time investigating, but things quickly go south when her older sister, an accomplished FBI BAU agent who constantly outshines her, is called in by local authorities to help. Making matters worse, the case brings up dark memories and buried secrets from her family's history-and neither May nor her sister are ready to confront the past. But with a ticking clock, May and her sister will have to put aside old grievances to find this killer and save the next victim, and they will have to be careful not to assume this is the same killer from their past. But is he? A suspenseful and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the May Moore series is a riveting mystery, packed with nonstop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you up listening late into the night.

Never Tell (May Moore Suspense Thriller, ,, 2022)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. Victims are found murdered nearby a new, ritzy hotel chain that has bought up lakeside property and infuriated locals. Red herrings abound, yet Deputy Sheriff May Moore believes this killer's motives may be far more complex. And that this killer may be far more sinister than anyone believes. Meanwhile, May's older sister, an accomplished FBI BAU agent, returns back home with shocking news, turning May's world upside down-while at the same time, new evidence pops up in the cold case of their sister. May will have to juggle all of this, though, with a killer who is on a rampage, and will stop at nothing until she brings him to justice. Is May up to the task? Or will she find herself his next target? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night. Book #3 in the series-NEVER LIVE-is also available.

Never Tell (May Moore Suspense Thriller, ,, 2022)
From #1 bestselling mystery and suspense author Blake Pierce comes a gripping new series: May Moore, 29, an average Midwestern woman and deputy sheriff, has always lived in the shadow of her older, brilliant FBI agent sister. Yet the sisters are united by the cold case of their missing younger sister-and when a new serial killer strikes in May's quiet, Minnesota lakeside town, it is May's turn to prove herself, to try to outshine her sister and the FBI, and, in this action-packed thriller, to outwit and hunt down a diabolical killer before he strikes again. "A masterpiece of thriller and mystery." -Books and Movie Reviews, Roberto Mattos (re Once Gone) ⭐⭐⭐⭐⭐ Victims are found murdered nearby a new, ritzy hotel chain that has bought up lakeside property and infuriated locals. Red herrings abound, yet Deputy Sheriff May Moore believes this killer's motives may be far more complex. And that this killer may be far more sinister than anyone believes. Meanwhile, May's older sister, an accomplished FBI BAU agent, returns back home with shocking news, turning May's world upside down-while at the same time, new evidence pops up in the cold case of their sister. May will have to juggle all of this, though, with a killer who is on a rampage, and will stop at nothing until she brings him to justice. Is May up to the task? Or will she find herself his next target? A page-turning and harrowing crime thriller featuring a brilliant and tortured Deputy Sheriff, the MAY MOORE series is a riveting mystery, packed with non-stop action, suspense, jaw-dropping twists, and driven by a breakneck pace that will keep you flipping pages late into the night.